British Columbia CARMA-CHIWOS Collaboration (BCC3): protocol for a community-collaborative cohort study examining healthy ageing with and for women living with HIV. Issue 8 (6th August 2021) - Swann, Shayda A; Kaida, Angela; Nicholson, Valerie; Brophy, Jason; Campbell, Amber R; Carter, Allison; Elwood, Chelsea; Gebremedhen, Tsion; Gormley, Rebecca; King, Elizabeth M; Lee, Melanie; Lee, Vonnie; et al.
Abstract : Introduction: Women living with HIV (WLWH) experience accelerated ageing and an increased risk of age-associated diseases earlier in life, compared with women without HIV. This is likely due to a combination of viral factors, gender differences, hormonal imbalance and psychosocial and structural conditions. This interdisciplinary cohort study aims to understand how biological, clinical and sociostructural determinants of health interact to modulate healthy ageing in WLWH. Methods and analysis: The British Columbia C hildren and Women: A ntiR etroviral therapy and M arkers of A ging-C anadian HI V W omen's Sexual and Reproductive Health Cohort S tudy (CARMA-CHIWOS) Collaboration (BCC3) study will enrol WLWH (n=350) and sociodemographically matched HIV-negative women (n=350) living in British Columbia. A subset of BCC3 participants will be past participants of CARMA, n≥1000 women and children living with and without HIV, 2008–2018 and/or CHIWOS, n=1422 WLWH, 2013–2018. Over two study visits, we will collect biological specimens for virus serologies, hormones and biological markers as well as administer a survey capturing demographic and sociostructural–behavioural factors. Sociodemographics, comorbidities, number and type of chronic/latent viral infections and hormonal irregularities will be compared between the two groups. Their association with biological markers and psychostructural and sociostructural factors will be investigated through multivariable regression and structural equation modelling. Retrospective longitudinal analyses will be conducted on data from past CARMA/CHIWOS participants. As BCC3 aims to follow participants as they age, this protocol will focus on the first study visits. Ethics and dissemination: This study has been approved by the University of British Columbia Children's and Women's Research Ethics Board (H19-00896). Results will be shared in peer-reviewed journals, conferences and at community events as well as at www.hivhearme.ca and @HIV_HEAR_me. WLWH are involved in study design, survey creation, participant recruitment, data collection and knowledge translation. A Community Advisory Board will advise the research team throughout the study.